## Abstract

There are several ways to quantify over public announcements. The most notable are reflected in arbitrary, group, and coalition announcement logics (APAL, GAL, and CAL correspondingly), with the latter being the least studied so far. In the present work, we consider coalition announcements through the lens of group announcements, and provide a complete axiomatisation of a logic with coalition announcements. To achieve this, we employ a generalisation of group announcements. Moreover, we study some logical properties of both coalition and group announcements that have not been studied before.

This is a preview of subscription content, access via your institution.

## Notes

A counterexample was given by Louwe Kuijer and can be found at https://personal.us.es/hvd/APAL_counterexample.pdf.

As any formula of \({\mathcal {L}}_{PAL}\) can be translated into an equivalent formula of \({\mathcal {L}}_{EL}\) (Plaza 2007), for succinctness’ sake, we use the former rather than the latter in the scope of knowledge modalities in group announcements.

The original idea of an infinite-grid counterexample is by Tim French (personal communication). Here we present its finite and reworked version.

French et al. (2019) use the same operators under the name of ‘half-coalition’ announcements. In this paper we use different syntax, which we think is more succinct.

## References

Ågotnes, T., & van Ditmarsch, H. (2008). Coalitions and announcements. In L. Padgham, D. C. Parkes, J. P. Müller, & S. Parsons, (Eds.),

*Proceedings of the 7th AAMAS*(pp. 673–680). IFAAMAS.Ågotnes, T., Balbiani, P., van Ditmarsch, H., & Seban, P. (2010). Group announcement logic.

*Journal of Applied Logic*,*8*(1), 62–81.Ågotnes, T., & van Ditmarsch, H. (2011). What will they say? Public announcement games.

*Synthese*,*179*(1), 57–85.Ågotnes, T., van Ditmarsch, H., & French, T. (2016). The undecidability of quantified announcements.

*Studia Logica*,*104*(4), 597–640.Ågotnes, T., & Wáng, Y. N. (2017). Resolving distributed knowledge.

*Artificial Intelligence*,*252*, 1–21.Balbiani, P. (2015). Putting right the wording and the proof of the truth lemma for APAL.

*Journal of Applied Non-Classical Logics*,*25*(1), 2–19.Balbiani, P., Baltag, A., van Ditmarsch, H., Herzig, A., Hoshi, T., & de Lima, T. (2008). Knowable’ as ‘known after an announcement.

*Review of Symbolic Logic*,*1*(3), 305–334.Balbiani, P., & van Ditmarsch, H. (2015). A simple proof of the completeness of APAL.

*Studies in Logic*,*8*(1), 65–78.Baltag, A., Özgün, A., & Sandoval, A. L. V. (2018). APAL with memory is better. In L. S. Moss, R. J. G. B. de Queiroz, & M. Martínez (Eds.),

*Proceedings of the 25th WoLLIC*(pp. 106–129).van Benthem, J. (2001). Games in dynamic-epistemic logic.

*Bulletin of Economic Research*,*53*(4), 219–248.van Benthem, J. (2014).

*Logic in Games*. Cambridge: MIT Press.van Benthem, J., van Eijck, J., & Kooi, B. (2006). Logics of communication and change.

*Information and Computation*,*204*(11), 1620–1662.Blackburn, P., de Rijke, M., & Venema, Y. (2001).

*Modal Logic*, volume 53 of*Cambridge Tracts in Theoretical Computer Science*. Cambridge University Press.Bozzelli, L., van Ditmarsch, H., French, T., Hales, J., & Pinchinat, S. (2014). Refinement modal logic.

*Information and Computation*,*239*, 303–339.Brogaard, B., & Salerno, J. (2013). Fitch’s paradox of knowability. In E. N. Zalta, (Ed.),

*The Stanford Encyclopedia of Philosophy*.van Ditmarsch, H. (2012). Quantifying notes. In C. L. Ong, & R. J. G. B. de Queiroz (Eds.),

*Proceedings of the 18th WoLLIC*(pp. 89–109).van Ditmarsch, H., Fernández-Duque, D., & van der Hoek, W. (2014). On the definability of simulation and bisimulation in epistemic logic.

*Journal of Logic and Computation*,*24*(6), 1209–1227.van Ditmarsch, H., & French, T. (2017). Quantifying over Boolean announcements.

*CoRR*, arXiv:1712.05310.van Ditmarsch, H., van der Hoek, W., & Kooi, B. (2008).

*Dynamic Epistemic Logic*, volume 337 of*Synthese Library*. Springer.van Ditmarsch, H., van der Hoek, W., Kooi, B., & Kuijer, L. B. (2017). Arbitrary arrow update logic.

*Artificial Intelligence*,*242*, 80–106.van Ditmarsch, H., van der Hoek, W., & Kuijer, L. B. (2016). Fully arbitrary public announcements. In L. D. Beklemishev, S. Demri, & A. Maté, (Eds.),

*Proceedings of the 11th AiML*(pp. 252–267). College Publications.Fan, J. (2016). Removing your ignorance by announcing group ignorance: A group announcement logic for ignorance.

*Studies in Logic*,*9*(4), 4–33.French, T., Galimullin, R., van Ditmarsch, H., & Alechina, N. (2019). Groups versus coalitions: On the relative expressivity of GAL and CAL. In N. Agmon, E. Elkind, M. E. Taylor, & M. Veloso (Eds.),

*Proceedings of the 18th AAMAS*(pp. 953–961).Galimullin, R. (2019).

*Coalition Announcements*. PhD thesis, University of Nottingham.Galimullin, R., & Alechina, N. (2017). Coalition and group announcement logic. In J. Lang, (Ed.),

*Proceedings of the 16th TARK*, volume 251 of*EPTCS*(pp. 207–220).Galimullin, R., Ågotnes, T., & Alechina, N. (2019). Group announcement logic with distributed knowledge. In P. Blackburn, E. Lorini, & M. Guo, (Eds.),

*Proceedings of the 7th LORI*, volume 11813 of*LNCS*(pp. 98–111). Springer.Galimullin, R., Alechina, N., & van Ditmarsch, H. (2018). Model checking for coalition announcement logic. In F. Trollmann, & A.-Y. Turhan, (Eds.),

*KI 2018: Advances in artificial intelligence*, volume 11117 of*LNCS*(pp. 11–23). Springer.Goldblatt, R. (1982).

*Axiomatising the Logic of Computer Programming*, volume 130 of*LNCS*. Springer.Goranko, V., & Otto, M. (2007). Model theory of modal logic. In P. Blackburn, J. van Benthem, & F. Wolter, (Eds.),

*Handbook of Modal Logic*, volume 3 of*Studies in Logic and Practical Reasoning*(pp. 249–329). Elsevier.Hales, J. (2013). Arbitrary action model logic and action model synthesis. In

*Proceedings of the 28th LICS*(pp. 253–262). IEEE Computer Society.Harel, D., Kozen, D., & Tiuryn, J. (2000).

*Dynamic logic*. Cambridge: MIT Press.Kuijer, L. B. (2017). Arbitrary arrow update logic with common knowledge is neither RE nor co-RE. In Lang, J., editor,

*Proceedings of the 16th TARK*, volume 251 of*EPTCS*(pp. 373–381).de Lima, T. (2014). Alternating-time temporal dynamic epistemic logic.

*Journal of Logic and Computation*,*24*(6), 1145–1178.Meyer, J.-J. Ch., & van der Hoek, W. (1995).

*Epistemic Logic for AI and Computer Science*, volume 41 of*Cambridge tracts in theoretical computer science*. Cambridge University Press.Pauly, M. (2002). A modal logic for coalitional power in games.

*Journal of Logic and Computation*,*12*(1), 149–166.Plaza, J. (2007). Logics of public communications.

*Synthese*,*158*(2), 165–179.Vanderschraaf, P., & Sillari, G. (2014). Common knowledge. In E. N. Zalta, (Ed.),

*The Stanford encyclopedia of philosophy*.Wang, Y., & Aucher, G. (2013). An alternative axiomatization of DEL and its applications. In F. Rossi (Ed.),

*Proceedings of the 23rd IJCAI*(pp. 1139–1146).Wáng, Y. N., & Ågotnes, T. (2013). Public announcement logic with distributed knowledge: Expressivity, completeness and complexity.

*Synthese*,*190*(1), 135–162.Wang, Y., & Cao, Q. (2013). On axiomatizations of public announcement logic.

*Synthese*,*190*(1), 103–134.

## Acknowledgements

I am very grateful to Natasha Alechina for her help with the previous, conference, version of this paper, and her comments on the current, journal, one. I would also like to thank Thomas Ågotnes, Hans van Ditmarsch, and Tim French for discussions of different parts of this paper on various occasions. Finally, I thank two anonymous reviewers of this journal. Their comments and corrections helped to make this paper both more readable and technically sound.

## Author information

### Authors and Affiliations

### Corresponding author

## Additional information

### Publisher's Note

Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

This paper is partially based on Galimullin and Alechina (2017) (and its corrected version available at Arxiv:1810.02769. Section 3, apart from Propositions 4 and 11, is entirely new. The axiomatisation and the completeness proof in Section 4 are also new, and many overlapping results (e.g. the Lindenbaum Lemma) are significantly improved.

## Appendices

### Appendix A: Coalition Annoucement Logic Subsumes Coalition Logic

It is known (Ågotnes and van Ditmarsch 2008) that CAL subsumes CL, i.e. all axioms of CL are valid in CAL, and rules of inference of CL are validity preserving in CAL. However, to the best of our knowledge, a formal proof has not yet been presented.

### Proposition 18

All of the following are valid and validity preserving in CAL.

\(\begin{array}{ll} (C0) &{}\text {all instantiations of propositional tautologies},\\ (C1) &{}\lnot \langle \! [ G ] \! \rangle \bot , \\ (C2) &{}\langle \! [ G ] \! \rangle \top , \\ (C3) &{}\lnot \langle \! [ \emptyset ] \! \rangle \lnot \varphi \rightarrow \langle \! [ A ] \! \rangle \varphi ,\\ (C4) &{}\langle \! [ G ] \! \rangle (\varphi _1 \wedge \varphi _2) \rightarrow \langle \! [ G ] \! \rangle \varphi _1, \\ (C5) &{}\langle \! [ G ] \! \rangle \varphi _1 \wedge \langle \! [ H ] \! \rangle \varphi _2 \rightarrow \langle \! [ G \cup H ] \! \rangle (\varphi _1 \wedge \varphi _2),\text { if } G \cap H = \emptyset , \\ (R0) &{}\vdash \varphi , \varphi \rightarrow \psi \Rightarrow \, \vdash \psi ,\\ (R1) &{} \vdash \varphi \leftrightarrow \psi \Rightarrow \, \vdash \langle \! [ G ] \! \rangle \varphi \leftrightarrow \langle \! [ G ] \! \rangle \psi . \end{array}\)

### Proof

*C*0 and *R*0 are obvious.

*C*1: It holds that \(\models \top \), and \(\top \) is true in every restriction of a model, i.e. \(\models [ \psi ] \top \). In particular, for some model \(M_s\) and all true formulas \(\psi _G\) and \(\chi _{A {\setminus } G}\): \(M_s \models \langle \psi _G \wedge \chi _{A {\setminus } G} \rangle \top \). We can relax the requirement of \(\psi _G\) being true by adding the formula as an antecedent. Formally, for all (true and false) \(\psi _G\) and some (true) \(\chi _{A {\setminus } G}\): \(M_s \models \psi _G \rightarrow \langle \psi _G \wedge \chi _{A {\setminus } G} \rangle \top \). The latter is \(M_s \models [ \! \langle G \rangle \! ] \top \) by the semantics, and this is equivalent to \(M_s \models \lnot \langle \! [ G ] \! \rangle \bot \) by the duality of the coalition announcement operators.

*C*2: For any pointed model \(M_s\) and any announcement \(\psi _G \wedge \chi _{A {\setminus } G}\) it holds that \(M_s \models [\psi _G \wedge \chi _{A {\setminus } G}] \top \). The latter implies that for some true \(\psi _G\) and for all \(\chi _{A {\setminus } G}\): \(M_s \models \psi _G \wedge [\psi _G \wedge \chi _{A {\setminus } G}] \top \), which is \(M_s \models \langle \! [ G ] \! \rangle \top \) by the semantics.

*C*3: Let \(\lnot \langle \! [ \emptyset ] \! \rangle \lnot \varphi \) be true in some arbitrary pointed model \(M_s\). This is equivalent to \(\exists \psi _A\): \(M_s \models \lnot [ \psi _A ] \lnot \varphi \), which is \(M_s \models \langle \! [ A ] \! \rangle \varphi \) by the semantics.

*C*4: Suppose that for some \(M_s\), \(M_s \models \langle \! [ G ] \! \rangle (\varphi _1 \wedge \varphi _2)\) holds. By the semantics, \(\exists \psi _G, \forall \chi _{A {\setminus } G}\): \(M_s \models \psi _G \wedge [\psi _G \wedge \chi _{A {\setminus } G}] (\varphi _1 \wedge \varphi _2)\). Then, by the axiom of PAL \([\psi ](\varphi \wedge \chi ) \leftrightarrow [\psi ] \varphi \wedge [\psi ] \chi \), we have \(\exists \psi _G, \forall \chi _{A {\setminus } G}\): \(M_s \models \psi _G \wedge [\psi _G \wedge \chi _{A {\setminus } G}] \varphi _1 \wedge [\psi _G \wedge \chi _{A {\setminus } G}] \varphi _2\). The latter implies \(\exists \psi _G, \forall \chi _{A {\setminus } G}\): \(M_s \models \psi _G \wedge [\psi _G \wedge \chi _{A {\setminus } G}] \varphi _1\), which is \(M_s \models \langle \! [ G ] \! \rangle \varphi _1\) by the semantics.

*C*5: Assume that for some \(M_s\) we have that \(M_s \models \langle \! [ G ] \! \rangle \varphi _1 \wedge \langle \! [ H ] \! \rangle \varphi _2\). Let us consider the first conjunct \(M_s \models \langle \! [ G ] \! \rangle \varphi _1\). By the semantics it is equivalent to \(\exists \psi _G, \forall \chi _{A {\setminus } G}\): \(M_s \models \psi _G \wedge [ \psi _G \wedge \chi _{A {\setminus } G} ] \varphi _1\). Since \(G \cap H = \emptyset \), we can split \(\chi _{A {\setminus } G}\) into \(\chi _{H}\) and \(\chi _{A {\setminus } {G \cup H}}\). Thus we have that \(\exists \psi _G, \forall \chi _H, \forall \chi _{A {\setminus } {(G \cup H)}}\): \(M_s \models \psi _G \wedge [ \psi _G \wedge \chi _{H} \wedge \chi _{A {\setminus } (G \cup H)} ] \varphi _1\). The same holds for the second conjunct: \(\exists \psi _H, \forall \chi _G, \forall \chi _{A {\setminus } {(G \cup H)}}\): \(M_s \models \psi _H \wedge [ \psi _H \wedge \chi _{G} \wedge \chi _{A {\setminus } (G \cup H)} ] \varphi _2\). Since \(\chi _H\) (\(\chi _G\)) quantifies over all formulas known to *H* (*G*), we can substitute \(\chi _H\) (\(\chi _G\)) with \(\psi _H\) (\(\psi _G\)). Hence we have

By the axiom of PAL \([\psi ](\varphi \wedge \chi ) \leftrightarrow [\psi ] \varphi \wedge [\psi ] \chi \), we have that

and the latter is equivalent to \(M_s \models \langle \! [ G \cup H ] \! \rangle (\varphi _1 \wedge \varphi _2)\) by the semantics.

\(R1\): Assume that \(\models \varphi \leftrightarrow \psi \). This means that for any pointed model \(M_s\) the following holds: \(M_s \models \varphi \) if and only if \(M_s \models \psi \) (1). Now suppose that for some pointed model \(N_t\) it holds that \(N_t \models \langle \! [ G ] \! \rangle \varphi \). By the semantics, \(\exists \psi _G, \forall \chi _{A {\setminus } G}\): \(N_t \models \psi _G \wedge [\psi _G \wedge \chi _{A {\setminus } G}] \varphi \), which is equivalent to the following: \(N_t \models \psi _G\) and (\(N_t \models \psi _G \wedge \chi _{A {\setminus } G}\) implies \(N^{\psi _G \wedge \chi _{A {\setminus } G}}_t \models \varphi \)). By (1) we have that \(\exists \psi _G, \forall \chi _{A {\setminus } G}\): \(N_t \models \psi _G\) and (\(N_t \models \psi _G \wedge \chi _{A {\setminus } G}\) implies \(N^{\psi _G \wedge \chi _{A {\setminus } G}}_t \models \psi \)), which is \(N_t \models \langle \! [ G ] \! \rangle \psi \) by the semantics. Since \(N_t\) was arbitrary, we have that \(\models \langle \! [ G ] \! \rangle \varphi \rightarrow \langle \! [ G ] \! \rangle \psi \). The same argument holds in the other direction. \(\square \)

### Appendix B: Proofs from Sect. 4

**Proposition 14** *R*3 *and* *R*4 *are truth-preserving.*

### Proof

(*R*3) *Base case*. If for all \(\psi _G\) we have that \(M_s \models \chi \wedge [\psi _G \wedge \chi ] \varphi \), then this is equivalent to \(M_s \models [G, \chi ] \varphi \) by the semantics.

*Induction Hypothesis*. If for some \(M_s\) it holds that \(M_s \models \eta (\chi \wedge [\psi _G \wedge \chi ] \varphi )\) for all \(\psi _G\), then \(M_s \models \eta ([G, \chi ] \varphi )\).

*Case* \(\forall \psi _G\): \(\tau \rightarrow \eta (\chi \wedge [\psi _G \wedge \chi ] \varphi )\) for some \(\tau \in {\mathcal {L}}_{CoRGAL}\). This means that \(M_s \models \lnot \tau \) or \(M_s \models \eta (\chi \wedge [\psi _G \wedge \chi ] \varphi )\). By the induction hypothesis we have that \(M_s \models \lnot \tau \) or \(M_s \models \eta ([ G, \chi ] \varphi )\), which is equivalent to \(M_s \models \tau \rightarrow \eta ([ G, \chi ] \varphi )\).

*Case* \(\forall \psi _G\): \(K_a \eta (\chi \wedge [\psi _G \wedge \chi ] \varphi )\) for some \(a \in A\). By semantics we have that for every \(t \in S\): \(s \sim _a t\) implies \(M_t \models \eta (\chi \wedge [\psi _G \wedge \chi ] \varphi )\). By the induction hypothesis we conclude that for every \(t \in S\): \(s \sim _a t\) implies \(M_t \models \eta ([G, \chi ] \varphi )\), which is equivalent to \(M_s \models K_a \eta ([ G, \chi ] \varphi )\).

*Case* \(\forall \psi _G\): \([\tau ] \eta (\chi \wedge [\psi _G \wedge \chi ] \varphi )\) for some \(\tau \in {\mathcal {L}}_{CoRGAL}\). This means that \(M_s \models \tau \) implies \(M_s^\tau \models \eta (\chi \wedge [\psi _G \wedge \chi ] \varphi )\). By the induction hypothesis we have that \(M_s \models \tau \) implies \(M_s^\tau \models \eta ([ G, \chi ] \varphi )\), which is equivalent to \(M_s \models [\tau ] \eta ([ G, \chi ] \varphi )\).

(*R*4) *Base case*. If for all \(\psi _G\) we have that \(M_s \models \langle A {\setminus } G, \psi _G \rangle \varphi \), then this is equivalent to \(M_s \models [ \! \langle G \rangle \! ] \varphi \) by the semantics.

*Induction Hypothesis*. If for some \(M_s\) it holds that \(M_s \models \eta (\langle A {\setminus } G, \psi _G \rangle \varphi )\) for all \(\psi _G\), then \(M_s \models \eta ([ \! \langle G \rangle \! ] \varphi )\).

*Case* \(\forall \psi _G\): \(\tau \rightarrow \eta (\langle A {\setminus } G, \psi _G \rangle \varphi )\) for some \(\tau \in {\mathcal {L}}_{CoRGAL}\). This means that \(M_s \models \lnot \tau \) or \(M_s \models \eta (\langle A {\setminus } G, \psi _G \rangle \varphi )\). By the induction hypothesis we have that \(M_s \models \lnot \tau \) or \(M_s \models \eta ([ \! \langle G \rangle \! ] \varphi )\), which is equivalent to \(M_s \models \tau \rightarrow \eta ([ \! \langle G \rangle \! ] \varphi )\).

*Case* \(\forall \psi _G\): \(K_a \eta (\langle A {\setminus } G, \psi _G \rangle \varphi )\) for some \(a \in A\). By semantics we have that for every \(t \in S\): \(s \sim _a t\) implies \(M_t \models \eta (\langle A {\setminus } G, \psi _G \rangle \varphi )\). By the induction hypothesis we conclude that for every \(t \in S\): \(s \sim _a t\) implies \(M_t \models \eta ([ \! \langle G \rangle \! ] \varphi )\), which is equivalent to \(M_s \models K_a \eta ([ \! \langle G \rangle \! ] \varphi )\).

*Case* \(\forall \psi _G\): \([\tau ] \eta (\langle A {\setminus } G, \psi _G \rangle \varphi )\) for some \(\tau \in {\mathcal {L}}_{CoRGAL}\). This means that \(M_s \models \tau \) implies \(M_s^\tau \models \eta (\langle A {\setminus } G, \psi _G \rangle \varphi )\). By the induction hypothesis we have that \(M_s \models \tau \) implies \(M_s^\tau \models \eta ([ \! \langle G \rangle \! ] \varphi )\), which is equivalent to \(M_s \models [\tau ] \eta ([ \! \langle G \rangle \! ] \varphi )\). \(\square \)

**Lemma 4** *Let* \(\varphi , \psi , \chi \in {\mathcal {L}}_{CoRGAL}\). *The following inequalities hold.*

### Proof

The proof is straightforward. We just show cases 5 and 6.

5. Note that \([\! \langle \! \rangle \! ]\)-depth for both sides of the inequality is the same and equals \(d_{[ \! \langle \! \rangle \! ]}(\chi ) + d_{[ \! \langle \! \rangle \! ]} (\varphi )\). In particular, we have the following for the left-hand side: \(d_{[ \! \langle \! \rangle \! ]} (\chi \wedge [\psi _G \wedge \chi ] \varphi )\) \(=\) \(\text {max}\{d_{[ \! \langle \! \rangle \! ]} (\chi ), d_{[ \! \langle \! \rangle \! ]} ([\psi _G \wedge \chi ] \varphi )\} = d_{[ \! \langle \! \rangle \! ]} ([\psi _G \wedge \chi ] \varphi ) = d_{[ \! \langle \! \rangle \! ]} (\psi _G \wedge \chi ) + d_{[ \! \langle \! \rangle \! ]} (\varphi ) = \text {max}\{d_{[ \! \langle \! \rangle \! ]} (\psi _G), d_{[ \! \langle \! \rangle \! ]}(\chi )\}\) \(+\) \(d_{[ \! \langle \! \rangle \! ]} (\varphi ) = d_{[ \! \langle \! \rangle \! ]} (\chi ) + d_{[ \! \langle \! \rangle \! ]} (\varphi )\). For the right-hand side we have that \(d_{[ \! \langle \! \rangle \! ]} ([G, \chi ] \varphi ) = d_{[ \! \langle \! \rangle \! ]}(\chi ) + d_{[ \! \langle \! \rangle \! ]} (\varphi )\).

Since \([ \! \langle \! \rangle \! ]\)-depths are the same, we calculate [, ]-depths. For the left-hand side we have that \(d_{[,]} (\chi \wedge [\psi _G \wedge \chi ]\varphi ) = d_{[,]} (\chi ) + d_{[,]} (\varphi )\). In particular, \(d_{[,]} (\chi \wedge [\psi _G \wedge \chi ]\varphi ) =\) \(\text {max} \{d_{[,]} (\chi ),\) \(d_{[,]} ([\psi _G \wedge \chi ]\varphi )\} =\) \(d_{[,]} ([\psi _G \wedge \chi ]\varphi )=\) \(d_{[,]} (\psi _G \wedge \chi ) + d_{[,]} (\varphi ) = \) \(\text {max}\{d_{[,]}(\psi _G), d_{[,]} (\chi )\} + d_{[,]} (\varphi )= \) \(d_{[,]} (\chi ) + d_{[,]} (\varphi )\). Depth of the right-hand side formula is \(d_{[,]} ([G, \chi ]\varphi ) = \) \(1 + d_{[,]} (\varphi ) + d_{[,]} (\chi )\). Hence, \(\chi \wedge [\psi _G \wedge \chi ]\varphi <^{Size}_{[,], [ \! \langle \! \rangle \! ]} [G, \chi ]\varphi \).

6. On the left-hand side we have that \(d_{[ \! \langle \! \rangle \! ]} (\langle A {\setminus } G, \psi _G \rangle \varphi ) =\) \(d_{[ \! \langle \! \rangle \! ]} (\varphi )\), and on the right-hand side the depth is \(d_{[ \! \langle \! \rangle \! ]} [ \! \langle G \rangle \! ] \varphi = \) \(d_{[ \! \langle \! \rangle \! ]} (\varphi ) + 1\). Hence, \(\langle A {\setminus } G, \psi _G \rangle \varphi <^{Size}_{[,], [ \! \langle \! \rangle \! ]} [ \! \langle G \rangle \! ] \varphi \). \(\square \)

**Lemma 6** *Let* \(\varphi , \psi \in {\mathcal {L}}_{CoRGAL}\). *If* \(\varphi \rightarrow \psi \) *is a theorem, then* \(\eta (\varphi ) \rightarrow \eta (\psi )\) *is a theorem as well.*

### Proof

Assume that \(\varphi \rightarrow \psi \) is a theorem. We prove the lemma by induction on \(\eta \).

*Base case* \(\eta {{:}{=}} \sharp \). Formula \(\varphi \rightarrow \psi \) is a theorem by assumption.

*Induction Hypothesis*. Assume that for some \(\eta \), \(\eta (\varphi ) \rightarrow \eta (\psi )\) is a theorem.

*Case* \((\tau \rightarrow \eta (\varphi )) \rightarrow (\tau \rightarrow \eta (\psi ))\) for some \(\tau \in {\mathcal {L}}_{CoRGAL}\). Formula \((\eta (\varphi ) \rightarrow \eta (\psi )) \rightarrow ((\tau \rightarrow \eta (\varphi )) \rightarrow (\tau \rightarrow \eta (\psi )))\) is a propositional tautology, and, hence, a theorem of CoRGAL. Using the induction hypothesis and *R*0, we have that \((\tau \rightarrow \eta (\varphi )) \rightarrow (\tau \rightarrow \eta (\psi ))\) is a theorem.

*Case* \(K_a \eta (\varphi ) \rightarrow K_a \eta (\psi )\) for some \(a \in A\). Since \(\eta (\varphi ) \rightarrow \eta (\psi )\) is a theorem by the induction hypothesis, \(K_a (\eta (\varphi ) \rightarrow \eta (\psi ))\) is also a theorem by *R*1. Next, \(K_a (\eta (\varphi ) \rightarrow \eta (\psi )) \rightarrow (K_a \eta (\varphi ) \rightarrow K_a \eta (\psi ))\) is an instance of *A*1, and, hence, a theorem. Finally, using *R*0 we have that \(K_a \eta (\varphi ) \rightarrow K_a \eta (\psi )\) is a theorem.

*Case* \([\tau ] \eta (\varphi ) \rightarrow [\tau ] \eta (\psi )\) for some \(\tau \in {\mathcal {L}}_{CoRGAL}\). Since \(\eta (\varphi ) \rightarrow \eta (\psi )\) is a theorem by the induction hypothesis, \([\tau ] (\eta (\varphi ) \rightarrow \eta (\psi ))\) is also a theorem by *R*2. Formula \([\tau ](\eta (\varphi ) \rightarrow \eta (\psi )) \rightarrow ([\tau ]\eta (\varphi ) \rightarrow [\tau ]\eta (\psi ))\) is implied by axiom schema *A*5. Using *R*0 we can conclude that \([\tau ]\eta (\varphi ) \rightarrow [\tau ]\eta (\psi )\) is a theorem of CoRGAL. \(\square \)

**Lemma 7** *Let* \(x\) *be a theory,* \(\varphi , \psi \in {\mathcal {L}}_{CoRGAL}\), *and* \(a \in A\). *The following are theories:* \(x + \varphi = \{\psi \mid \varphi \rightarrow \psi \in x\}, K_a x = \{\varphi \mid K_a \varphi \in x\}\), *and* \([\varphi ]x = \{\psi \mid [\varphi ]\psi \in x\}\).

### Proof

Let \(\psi \) be a theorem, i.e. \(\psi \in \mathrm {CoRGAL}\). Then \(\varphi \rightarrow \psi \) is also a theorem, since \(\psi \rightarrow (\varphi \rightarrow \psi ) \in \mathrm {CoRGAL}\) and CoRGAL is closed under *R*0. Moreover, \(K_a \psi \) and \([\varphi ] \psi \) are theorems as well due to the fact that CoRGAL is closed under *R*1 and *R*2. Therefore, \(\psi \in x + \varphi \), \(\psi \in K_a x\), and \(\psi \in [\varphi ] x\), and hence \(\mathrm {CoRGAL} \subseteq x + \varphi , K_a x, [\varphi ] x\).

The rest of the proof is an extension of the one from Balbiani et al. (2008), where it was shown that \(x + \varphi \), \(K_a x\), and \([\varphi ] x\) are closed under *R*0. We argue that corresponding sets are closed under *R*3 and *R*4.

*Case* \(x + \varphi \). Suppose that \(\eta (\chi \wedge [\psi _G \wedge \chi ]\tau ) \in x + \varphi \) for some given \(\chi \), for all \(\psi _G\), and for some \(\tau \in {\mathcal {L}}_{CoRGAL}\). This means that \(\varphi \rightarrow \eta (\chi \wedge [\psi _G \wedge \chi ]\tau ) \in x\) for all \(\psi _G\). Since \(\varphi \rightarrow \eta (\chi \wedge [\psi _G \wedge \chi ]\tau )\) is a necessity form, and \(x\) is closed under \(R3\) (by Definition 16), we infer that \(\varphi \rightarrow \eta ([G, \chi ] \tau ) \in x\), and, consequently, \(\eta ([G, \chi ] \tau ) \in x + \varphi \). So, \(x + \varphi \) is closed under \(R3\).

Now, let \(\forall \psi _G\): \(\eta (\langle A {\setminus } G, \psi _G \rangle \tau ) \in x + \varphi \). By the definition of \(x+\varphi \) this means that \(\varphi \rightarrow \eta (\langle A {\setminus } G, \psi _G \rangle \tau ) \in x\) for all \(\psi _G\). Since \(\varphi \rightarrow \eta (\langle A {\setminus } G, \psi _G \rangle \tau \) is a necessity form and *x* is closed under *R*4, we infer that \(\varphi \rightarrow \eta ( [ \! \langle G \rangle \! ] \tau ) \in x\), and, consequently, \(\eta ( [ \! \langle G \rangle \! ] \tau ) \in x + \varphi \). So, \(x + \varphi \) is closed under \(R4\).

*Case* \(K_a x\). Suppose that \(\eta (\chi \wedge [\psi _G \wedge \chi ]\tau ) \in K_a x\) for some given \(\chi \), for all \(\psi _G\), and for some \(\tau \in {\mathcal {L}}_{CoRGAL}\). This means that \(K_a \eta (\chi \wedge [\psi _G \wedge \chi ]\tau ) \in x\) for all \(\psi _G\). Since \(K_a \eta (\chi \wedge [\psi _G \wedge \chi ]\tau )\) is a necessity form, and \(x\) is closed under \(R3\) (by Definition 16), we infer that \(K_a \eta ([G, \chi ] \tau ) \in x\), and, consequently, \(\eta ([G, \chi ] \tau ) \in K_a x\). So, \(K_a x\) is closed under \(R3\).

Now, let \(\forall \psi _G\): \(\eta (\langle A {\setminus } G, \psi _G \rangle \tau ) \in K_a x\). By the definition of \(K_a x\) this means that \(K_a \eta (\langle A {\setminus } G, \psi _G \rangle \tau ) \in x\) for all \(\psi _G\). Since \(K_a \eta (\langle A {\setminus } G, \psi _G \rangle \tau \) is a necessity form and *x* is closed under *R*4, we infer that \(K_a \eta ( [ \! \langle G \rangle \! ] \tau ) \in x\), and, consequently, \(\eta ( [ \! \langle G \rangle \! ] \tau ) \in K_a x\). So, \(K_a x\) is closed under \(R4\).

*Case* \([\varphi ] x\). Finally, suppose that \(\eta (\chi \wedge [\psi _G \wedge \chi ]\tau ) \in [\varphi ] x\) for some given \(\chi \), for all \(\psi _G\), and for some \(\tau \in {\mathcal {L}}_{CoRGAL}\). This means that \([\varphi ] \eta (\chi \wedge [\psi _G \wedge \chi ]\tau ) \in x\) for all \(\psi _G\). Since \([\varphi ] \eta (\chi \wedge [\psi _G \wedge \chi ]\tau )\) is a necessity form, and \(x\) is closed under \(R3\) (by Definition 16), we infer that \([\varphi ] \eta ([G, \chi ] \tau ) \in x\), and, consequently, \(\eta ([G, \chi ] \tau ) \in [\varphi ] x\). So, \([\varphi ] x\) is closed under \(R3\).

Now, let \(\forall \psi _G\): \(\eta (\langle A {\setminus } G, \psi _G \rangle \tau ) \in [\varphi ] x\). By the definition of \([\varphi ] x\) this means that \([\varphi ] \eta (\langle A {\setminus } G, \psi _G \rangle \tau ) \in x\) for all \(\psi _G\). Since \([\varphi ] \eta (\langle A {\setminus } G, \psi _G \rangle \tau \) is a necessity form and *x* is closed under *R*4, we infer that \([\varphi ] \eta ( [ \! \langle G \rangle \! ] \tau ) \in x\), and, consequently, \(\eta ( [ \! \langle G \rangle \! ] \tau ) \in [\varphi ] x\). So, \([\varphi ] x\) is closed under \(R4\). \(\square \)

## Rights and permissions

## About this article

### Cite this article

Galimullin, R. Coalition and Relativised Group Announcement Logic.
*J of Log Lang and Inf* **30**, 451–489 (2021). https://doi.org/10.1007/s10849-020-09327-2

Accepted:

Published:

Issue Date:

DOI: https://doi.org/10.1007/s10849-020-09327-2

### Keywords

- Dynamic epistemic logic
- Public announcement logic
- Group announcement logic
- Coalition announcement logic